Nature seekers within the urban vicinity - Z., Rosilawati; Nordin, Nikmatul Adha; Sandri, Dian; Ahmad, Faizah; Mohd@Ahmad, Ibrahim (Journal of Surveying, Construction and Property, 2017)
This paper presents visitors’ profile and motivation to Broga Hill, a nature-based attraction located at the fringe of Kuala Lumpur the capital city of Malaysia. The paper seeks to examine visitors’ motivation for visiting the study area. The study adopts quantitative approach through self-administered questionnaire surveys and interviews. 100 respondents were randomly selected among those who visited Broga Hill. Non parametric tests were used to analyse the data since it was found to be not normally distributed. The findings reveals that Broga Hill is visited by nature seekers of various backgrounds who were willing to spend almost forty minutes to one hour climbing up the hill because of the fresh air and the beautiful scenery from the hilltop. These are the pull factors that motivate visitors’ attraction to the hill. The paper concludes that natural forest within the urban vicinity such as Broga Hill should be preserved. Any new development encroaching green spaces within any urban vicinity should be reviewed rigorously. Keywords: nature seekers; motivation; typology; recreation; push and pull